Evaluation of Interhandle Distance During Pushing and Pulling of a Four-Caster Cart for Upper Limb Exertion - Akihiro Ohnishi; Masato Takanokura; Atsushi Sugama (Elsevier, 2016)
Background: This study examined the relationship between interhandle distances and upper limb exertion during simply pushing and pulling of a cart with four swivel wheels, defined by a roll box pallet (RBP) in a Japanese industrial standard. Methods: Six healthy young male participants were asked to push and pull an RBP at a distance of 5.2 m under six conditions corresponding to different interhandle distances (40 cm, 60 cm, and 80 cm) and weights (130 kg and 250 kg). The upper limb exertion was studied by shoulder abduction and flexion, and elbow flexion, as well as surface electromyogram (EMG) in shoulder extensor, and elbow flexor and extensor. Participants were required to provide subjective evaluations on operability after each trial. Results: Subjective operability indicated that a narrower interhandle distance had a better operability for pushing. Interhandle distance was also related to upper limb exertion especially for pushing. A narrow interhandle distance caused smaller shoulder adduction but larger elbow flexion. The normalized EMG data revealed that muscular activity became smaller with a narrow interhandle distance in shoulder extensor. During the pulling task, elbow flexion was smaller at a narrow interhandle distance, although subjective operability and normalized EMG were not significantly varied. Conclusion: A wider interhandle distance, such as 80 cm, was not suitable in the forwardbackward movement of the RBP. Therefore, this study concluded that an interhandle distance of 40 cm would be suitable for pushing and pulling an RBP to protect the workers' hands against the risk of injury by installing inner handles.